Effect of strength training on elderly blood pressure: a narrative literature (Research, Society and Development, 2022)
The aim of the present study was to review the effects of strength training on elderly blood pressure. A search was performed in the SciELO and Google Scholar databases between 2010 and 2021 using the descriptors “strength training”, “cardiovascular health”, “blood pressure” and “elderly”. Articles were analyzed based on the inclusion and exclusion criteria and thus we included 4 articles in this review, which mostly indicate that strength training promotes control in blood pressure values in the elderly. The results suggest that resistance training can help to control systemic arterial hypertension in the elderly, as well as antihypertensive medications. Thus, the authors recommend the inclusion of strength exercises within the non-pharmacological planning of blood pressure control.